Ekonomi Biru sebagai Upaya Pembangunan Berkelanjutan dan Pemenuhan Hak Asasi Manusia - Dessy Maeyangsari (Perspektif Hukum, 2023)
Blue Economy is a concept of the use of marine resources for the economic growth, the improvement of livelihood, along with the preservation of marine ecosystems. This article discusses the potential of the blue economy for sustainable development efforts that have been the focus of many countries since the 1972 Stockholm Environmental Conference. Basically, the use of marine resources has been regulated in the United Nations on the Law of the Sea 1982 and other international legal instruments. However, special management systems and regulations are needed at international and national levels to implement the components of Blue Economy activities that prioritize sustainable development and the preservation of the marine environment. In addition, another potential of the Blue Economy is its relation to the fulfilment of Human Rights in Indonesia, which will be reviewed normatively through national legislation and international law study.